2000
DOI: 10.1029/1999gl003733
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of equatorial electrojet in the mesospheric partial reflection drifts over magnetic equator

Abstract: Abstract. The partial reflection (PR) drifts at 98 km measured by the medium frequency (MF) radar operating at Tirunelveli, India, situated close to the magnetic equator, are shown to have the combined effects of mesospheric winds and the equatorial electrojet. The evidences for this behavior of the PR drifts are brought out from a detailed examination of the temporal variation of the dynamical and the geometrical parameters associated with the ground diffraction pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…On the other hand, when E sq was absent, the fading rates were too small implying slow fading, the drift direction was reversed to the east and the ground diffraction pattern was almost isotropic. The recent reports that made use of the MF radar observations from Tirunelveli were in conformity to the earlier HF spaced receiver findings (Gurubaran and Rajaram, 2000;Ramkumar et al, 2002;Gurubaran et al, 2007).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, when E sq was absent, the fading rates were too small implying slow fading, the drift direction was reversed to the east and the ground diffraction pattern was almost isotropic. The recent reports that made use of the MF radar observations from Tirunelveli were in conformity to the earlier HF spaced receiver findings (Gurubaran and Rajaram, 2000;Ramkumar et al, 2002;Gurubaran et al, 2007).…”
Section: Introductionsupporting
confidence: 82%
“…The MF radar operating at Tirunelveli has been providing useful data for more than a decade on mean winds, tides and planetary waves. Previous work using data from this site clearly revealed that the MF radar echoes at 90 km and above are influenced by electrodynamical processes (Gurubaran and Rajaram, 2000;Ramkumar et al, 2002;Gurubaran et al, 2007). For radar systems operating in the vicinity of the magnetic equator, complexities in interpreting the drift measurements in terms of neutral winds arise due to the presence of the equatorial electrojet (EEJ) that plays a dominant role in the generation and movement of electron density irregularities in the lower E region (Kelley, 1989).…”
Section: Introductionmentioning
confidence: 91%
“…Though winds are measured every 2 km, the data acceptance rate, which is based on several data rejection criteria (Briggs, 1984), is higher only above 84 km. Radar measurements at higher heights (above 92 km) are constrained by the influence of electric fields and the radar tends to measure the electron drift motion driven by intense electric field rather than the neutral wind (Gurubaran and Rajaram, 2000). The tidal amplitudes are computed using a least squares harmonic fit over a five-day window of hourly wind values, which is successively forwarded every one day.…”
Section: Mf Radar Windsmentioning
confidence: 99%
“…MF, meteor and MST radars are being used to measure neutral winds in the mesosphere–lower thermosphere (MLT) region (80–100 km) with the advantage of continuous observation over a particular site. Radars operating near the magnetic equator have complexities in interpreting the measurements in terms of neutral wind, since the plasma drifts at electrojet heights are expected to contaminate neutral wind measurements [ Briggs , 1977; Chang et al , 1999; Gurubaran and Rajaram , 2000]. In this context we revisit the interpretations made by Kumar et al [2007], in particular, the affirmation that the meteor system makes reliable wind measurements at heights above 90 km.…”
mentioning
confidence: 99%